Digital partisans: An inquiry on the use of bots for political propaganda in Mexico - David Ramírez Plascencia; Álvaro Ochoa Zuno; Rosa María Alonzo González (Revista Teknokultura)
In 2025, due to the popularization of AI applications such as ChatGPT, there has been a renewed interest in Artificial Intelligence. Politics have not been immune to this tendency. The presence of AI is seen as a promising tool to promote candidates and parties on social media, but also as a potential weapon that may be used to instigate misinformation and to deceive. This article is founded on the interception of artificial intelligence, disinformation, and media coverage. It covers a timeline of eight years, from 2016 to 2023. We focuse on AI bots in Mexico and its use in politics. Its objectives are to analyze how Mexican newspapers have portrayed the use of bots in national politics through content analysis techniques and framing theory, and to examine the evidence provided by media coverage regarding the existence of a bot market for politics in Mexico.